Penguatan Literasi Sains melalui Kegiatan Praktikum IPA pada Siswa SMPN 10 Palangka Raya - Yunus Pebriyanto; Vinsen Willi Wardhana; Yoan Theasy (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
SMP Negeri 10 Palangka Raya is an educational institution located within the administrative area of Palangka Raya City, Central Kalimantan Province; however, access to the school is only possible via river transportation. This geographical condition has contributed to limited development of students’ human resource capacities, particularly due to the inadequate availability of supporting facilities such as reliable internet access. Consequently, the school lags behind other institutions of the same level in terms of scientific literacy. In response to these challenges, the implementation team conducted a community service program as part of the Tri Dharma of Higher Education, focusing on strengthening students’ scientific literacy through hands-on science practicum activities. The program included providing students with practical learning experiences and donating laboratory equipment to enhance the effectiveness of science learning. The community service activities were carried out through four main stages: observation and coordination, socialization, mentoring and evaluation, and program sustainability planning. Based on the evaluation results, students demonstrated highly positive responses toward the activities. This indicates that the intervention through practicums and the provision of laboratory facilities successfully offered meaningful learning experiences, broadened students’ scientific perspectives, and contributed significantly to the improvement of their scientific literacy.